2017
DOI: 10.1172/jci.insight.92926
|View full text |Cite
|
Sign up to set email alerts
|

Lupus and proliferative nephritis are PAD4 independent in murine models

Abstract: Though recent reports suggest that neutrophil extracellular traps (NETs) are a source of antigenic nucleic acids in systemic lupus erythematosus (SLE), we recently showed that inhibition of NETs by targeting the NADPH oxidase complex via cytochrome b-245, β polypeptide (cybb) deletion exacerbated disease in the MRL.Faslpr lupus mouse model. While these data challenge the paradigm that NETs promote lupus, it is conceivable that global regulatory properties of cybb and cybb-independent NETs confound these findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 73 publications
(105 reference statements)
4
64
0
Order By: Relevance
“…Here, we show that genetic deletion of elane did not have any impact on clinical or immunological parameters of SLE in MRL.Fas lpr mice. Taken together with earlier work [22, 23, 26], these findings add additional evidence that challenges the concept that neutrophils and NETs, to the degree that NET generation and neutrophil effector function relies on PADI4 [713], ELANE [10, 1417], or CYBB [46], critically drives lupus.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Here, we show that genetic deletion of elane did not have any impact on clinical or immunological parameters of SLE in MRL.Fas lpr mice. Taken together with earlier work [22, 23, 26], these findings add additional evidence that challenges the concept that neutrophils and NETs, to the degree that NET generation and neutrophil effector function relies on PADI4 [713], ELANE [10, 1417], or CYBB [46], critically drives lupus.…”
Section: Introductionsupporting
confidence: 72%
“…This point, which is punctuated by the current data, along with the lack of a role for neutrophils per se in driving lupus, heralds a juncture at which the field should seriously reevaluate whether the “NETs drive lupus” hypothesis remains valid and whether blocking NET formation or neutrophil function makes sense as a therapeutic strategy. In contrast, multiple studies have shown regulatory roles in various systems for CYBB, and to an extent PAD4 and MPO, such that disease is exacerbated in their absence [22, 23, 26, 27, 59]. We would thus posit that neutrophils and their effector mechanisms, such as NET generation, may have evolved to protect us from autoimmune diseases, rather than function as vectors to promote them.…”
Section: Discussionmentioning
confidence: 96%
“…These observations have been supported by mouse studies in which pharmacologic inhibition of NET formation in lupus-prone mice, either by inhibition of PAD4 activity or by inhibition of mitochondrial ROS, ameliorates disease (34,35). However, an argument refuting the notion that NET formation is required for disease development has been made in genetic studies of MRL/lpr mice in which deficiency of either PAD4 or NOX-2 did not protect against disease (36,37).…”
Section: Neutrophils and Net Formationmentioning
confidence: 96%
“…These observations have been supported by mouse studies in which pharmacologic inhibition of NET formation in lupus-prone mice, either by inhibiting PAD4 activity or by inhibiting mitochondrial ROS, ameliorates disease, (34, 35). However, an argument against the requirement for NETs has been made by genetic studies in MRL.lpr mice where deficiency of either PAD4 or Nox2 did not protect against disease (36, 37). ROS generation is necessary for NET formation in most contexts and we and others recently demonstrated that ROS generation by mitochondria, rather than Nox2, is key to oxidation of DNA and in particular, mitochondrial DNA (mtDNA) (34, 38).…”
Section: How Cells Die Determines Non-inflammatory Versus Inflammatormentioning
confidence: 99%
“…Similar to Ncf1** mice, PAD4‐deficient mice exhibited higher autoantibody levels and enhanced proteinuria . In a parallel study by the Shlomchik lab, PAD4‐deficiency or pharmacological inhibition of PAD4 did not have any effect on tolerance loss, immune activation, or nephritis in the MRL. Fas lpr lupus model.…”
Section: Dealing With Danger Death and Collateral Damage—how Neutromentioning
confidence: 86%